Analysis of Student Errors in Solving Numeracy Literacy Problems of Graph Representation Model in Elementary School - Intan Sari Rufiana; Slamet Arifin; Mohammad Yusuf Randy; Fierda Nursitasari Amaliya (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis study aims to describe the types of student errors in solving numeracy literacy problems of graph representation models. This study used a mixed methods research design with a sequential exploratory type. The data collection techniques used were tests and interviews. The participants in this study were 30 elementary school students tested and six students selected by purposive sampling to be interviewed. The results showed that students experienced conceptual errors and procedural errors. In conceptual errors, 40% of students make errors in reading data, 43% between data, and 60% of students make errors beyond data. Conceptual errors occur when students cannot understand the context of the problem, cannot read the data, do not master the basic concepts of statistics, and do not understand number patterns. In procedural errors, 63% of students make errors in reading data, 73% of students make errors in reading between data, and 80% of students make errors in reading beyond data. Procedural errors occur when students are wrong in choosing the solution procedure, calculating, and predicting. Therefore, educators need to design appropriate learning strategies to minimize errors made by students in numeracy literacy questions on graph representation models, such as applying contextual learning-based numeracy problems.Keywords: student errors, graphic literacy, numeracy literacy, elementary school. AbstrakPenelitian ini bertujuan untuk mendeskripsikan jenis-jenis kesalahan siswa dalam menyelesaikan soal literasi numerasi model representasi grafik. Penelitian ini menggunakan desain penelitian mixed methods dengan tipe eksploratori sekuensial. Teknik pengumpulan data yang digunakan adalah tes dan wawancara. Partisipan dalam penelitian ini adalah 30 siswa sekolah dasar yang dites dan enam siswa yang dipilih secara purposive sampling untuk diwawancarai. Hasil penelitian menunjukkan bahwa siswa mengalami kesalahan konseptual dan kesalahan prosedural. Pada kesalahan konseptual, 40% siswa melakukan kesalahan dalam membaca data, 43% di antara data, dan 60% siswa melakukan kesalahan di luar data. Kesalahan konseptual terjadi ketika siswa tidak dapat memahami konteks soal, tidak dapat membaca data, tidak menguasai konsep dasar statistika, dan tidak memahami pola bilangan. Pada kesalahan prosedural, 63% siswa melakukan kesalahan dalam membaca data, 73% siswa melakukan kesalahan dalam membaca antar data, dan 80% siswa melakukan kesalahan dalam membaca di luar data. Kesalahan prosedural terjadi ketika siswa salah dalam memilih prosedur penyelesaian, menghitung, dan memprediksi. Oleh karena itu, pendidik perlu merancang strategi pembelajaran yang tepat untuk meminimalisir kesalahan yang dilakukan siswa dalam soal literasi numerasi pada model representasi grafik, seperti menerapkan soal literasi numerasi berbasis pembelajaran kontekstual.Kata kunci: kesalahan siswa, literasi grafik, literasi numerasi, sekolah dasar.